ANALISIS PEMBINAAN FIKIH KELUARGA BAGI SANTRI MELALUI PENDIDIKAN PRA NIKAH (STUDI DI YAYASAN PONDOK PESANTREN SUNAN DRAJAT BANJARWATI PACIRAN LAMONGAN) - Janeko Janeko; Anas Alhifni; M. Anang Hanifullah (Reflektika, 2026)
Family fikih guidance is a crucial aspect in preparing individuals for a harmonious and sustainable married life. Social reality shows that many family problems arise from a lack of understanding of family fikih among married couples before marriage. Therefore, premarital education is a strategic instrument in equipping prospective couples, especially Islamic boarding school students (santri), with a comprehensive religious understanding. This study aims to analyze family fikih guidance for Islamic boarding school students through premarital education at the Sunan Drajat Banjarwati Paciran Lamongan Islamic Boarding School Foundation, including the form and scope of material, guidance methods, and students' understanding after participating in premarital education. This study employed a qualitative approach with a descriptive-analytical approach. Data were obtained through observation, interviews, and documentation with students, premarital education counselors, and Islamic boarding school administrators. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that family fikih guidance through premarital education at the Sunan Drajat Islamic Boarding School Foundation is implemented in an integrated manner with Islamic boarding school traditions through the study of yellow books, discussions, role models, and religious advice. The guidance material covers the concept and purpose of marriage, the pillars and requirements of marriage, the rights and obligations of husband and wife, relationship patterns and household ethics, child rearing, and household problems. The guidance method is dominated by religious lectures, which are effective in instilling normative understanding and moral values, although more participatory and contextual methods are still needed. In terms of understanding, students demonstrated an increase in cognitive and affective understanding of family fikih, particularly regarding the purpose of marriage and family responsibilities. However, this understanding still tends to be normative and not fully applicable. This study concludes that premarital education in Islamic boarding schools plays a strategic role in fostering the Islamic jurisprudence (fikih) of Islamic students' families, but requires strengthening the material and methods to be more relevant to the challenges of contemporary families.